2020
DOI: 10.1093/treephys/tpaa089
|View full text |Cite
|
Sign up to set email alerts
|

Radial oxygen loss is correlated with nitrogen nutrition in mangroves

Abstract: The present study aimed to explore the possible functions of radial oxygen loss (ROL) on mangrove nutrition. A field survey was conducted to explore the relations among ROL, root anatomy and leaf N in different mangrove species along a continuous tidal gradient. Three mangroves with different ROL (Avicennia marina > Kandelia obovata > Rhizophora stylosa) were then selected to further explore the dynamics of N at root-soil interface. The results showed that seaward pioneer mangrove species such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 83 publications
3
14
0
Order By: Relevance
“…The presence of air lacunae implies that the middle cortex of seagrass rhizome may act as belowground oxygen storage ( Pedersen et al, 1998 ; Borum et al, 2005 ; Sand-Jensen et al, 2005 ). Similar observations were reported in the seagrasses C. rotundata and H. ovalis ( Roberts, McComb & Kuo, 1985 ; Pedersen et al, 1998 ; Connell, Colmer & Walker, 1999 ; Kuo & den Hartog, 2006 ) and in other wetland plants ( Cheng et al, 2020a ; Armstrong et al, 2000 ; Soukup, Votrubová & Čížková, 2002 ; Matthews & Seymour, 2014 ). It has been suggested that tissue porosity is associated with tolerance to hypoxic conditions ( Visser et al, 2000 ; Hasler-Sheetal et al, 2015 ; Cheng et al, 2020a ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The presence of air lacunae implies that the middle cortex of seagrass rhizome may act as belowground oxygen storage ( Pedersen et al, 1998 ; Borum et al, 2005 ; Sand-Jensen et al, 2005 ). Similar observations were reported in the seagrasses C. rotundata and H. ovalis ( Roberts, McComb & Kuo, 1985 ; Pedersen et al, 1998 ; Connell, Colmer & Walker, 1999 ; Kuo & den Hartog, 2006 ) and in other wetland plants ( Cheng et al, 2020a ; Armstrong et al, 2000 ; Soukup, Votrubová & Čížková, 2002 ; Matthews & Seymour, 2014 ). It has been suggested that tissue porosity is associated with tolerance to hypoxic conditions ( Visser et al, 2000 ; Hasler-Sheetal et al, 2015 ; Cheng et al, 2020a ).…”
Section: Discussionsupporting
confidence: 87%
“…These anatomical characteristics are tightly coupled to fundamental physiological functions of plants, such as cellular respiration and photosynthesis. Their roles in mediating plant stress tolerance have been extensively explored in many plant species ( Jensen et al, 2005 ; Pi et al, 2009 ; Jovanovic et al, 2015 ; Dai et al, 2017 ; Cheng et al, 2020a , 2020b ; de Lopes et al, 2020 ; Mei et al, 2020 ; Scholz et al, 2021 ). Studies in mangrove plants suggest that differences in both porosity and ROL barrier contribute to different sensitivity to waterlogging, root zone hypoxia, nutrient limitation and heavy metal stress ( Pi et al, 2009 ; Dai et al, 2017 ; Cheng et al, 2020a , 2020b ; Pedersen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mangrove sediments are rich in organic matter, they are generally nutrient-deficient. Nutrient limitations were also widely reported in mangrove forests (Feller et al, 2003;Reef et al, 2010;Wang and Gu, 2013;Cheng et al, 2020). Even worse, anaerobic conditions might further aggravate the enrichment of anaerobic microbes and reductive phytotoxins (e.g., CH 4 , H 2 S, and sulfides).…”
Section: Specific Microbial Taxa and Functional Potential In Maintaining Mangrove Survival And Successionmentioning
confidence: 97%
“…The adaptation and succession of mangroves in intertidal regions are speculated to be closely related to microbes in the sediments. Unfortunately, the potential roles of microbes and their functions in mangrove ecosystems are still poorly understood, although changes in vegetation during mangrove succession and how mangrove plants adapt to intertidal environmental adversities have been well studied ( Wang et al, 2019 ; Cheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%